Difference of Differentiation Composition Operators on the Fractional Cauchy Transforms Spaces. (10th September 2018) - Wang, Maofa; Guo, Xin
Abstract: In this paper, we consider the boundedness and compactness of the differences of differentiation composition operators from the space of fractional Cauchy transforms to the Bloch-type spaces and the weighted Dirichlet spaces. Surprisingly, these characterizations are free from pseudo-hyperbolic metric, which is a common feature of all the preceding characterizations of difference of differentiation composition operators on various spaces of holomorphic functions.